2013
DOI: 10.1309/ajcpwgg69mczowmm
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Activating Receptor, NKp46 (CD335), in Human Natural Killer and T-Cell Neoplasia

Abstract: Collectively, these data support the diagnostic utility of CD335 in evaluating hematopoietic malignancies and suggest that CD335 could be a useful target for selective immunotherapy in patients with mature NK and T-cell neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
(53 reference statements)
2
19
1
Order By: Relevance
“…The NK cell population diversity studies described above are in line with numerous other reports that changes in NK cell surface marker expression and relative KIR + NK cell frequencies occur in the settings of cancer and infection (Beziat et al, 2012; Beziat et al, 2013; Davis et al, 2015; Fauriat et al, 2007; Freud et al, 2013; Guma et al, 2004; Guma et al, 2006; Sun et al, 2012). Many such studies were originally performed and interpreted in the conceptual framework of the traditional CD56 bright and CD56 dim cNK dichotomy.…”
Section: Adaptive Nk Cellssupporting
confidence: 87%
“…The NK cell population diversity studies described above are in line with numerous other reports that changes in NK cell surface marker expression and relative KIR + NK cell frequencies occur in the settings of cancer and infection (Beziat et al, 2012; Beziat et al, 2013; Davis et al, 2015; Fauriat et al, 2007; Freud et al, 2013; Guma et al, 2004; Guma et al, 2006; Sun et al, 2012). Many such studies were originally performed and interpreted in the conceptual framework of the traditional CD56 bright and CD56 dim cNK dichotomy.…”
Section: Adaptive Nk Cellssupporting
confidence: 87%
“…This molecule may function in cell‐cell interactions in addition to its cytotoxic effects in the tumor environment. Recent study showed that NKp46 was detected in ALK + ALCL cells but not in EATL cells . Nevertheless, we observed that NKp46 was detected in some of the surrounding bystander cells but not in ALK + ALCL cells (Figure C).…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies showed that CD94, NKG2A, and NKp46 were usually detected in ENKL, whereas the expression of another group of NKR, the killer cell immunoglobulin‐like receptors seem to be reduced in most ENKL cases . The pathological implication of NKR in PTNKL remains to be defined.…”
Section: Introductionmentioning
confidence: 95%
“…NKp46 has been implicated as either a critical player in the progression and severity of different diseases, including type I diabetes, or as a prognostic marker in NK cell malignancies , and approximately 20% of T cell lymphomas . Consequently, we wanted to investigate whether our antibody has the potential to become a novel immunotherapeutic drug for the treatment of these diseases.…”
Section: Resultsmentioning
confidence: 99%